Improving High School Teacher Skills in Utilizing Learning Models in the Digital Era - Lalita Melasarianti; Etin Pujihastuti; Arfin Deri Listiandi; Didik Rilastiyo Budi; Rindha Widyaningsih; Septi Mariasari (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The learning model continues to evolve with the times. The learning model is one of the learning tools that support the teaching and learning process. The problem that exists at SMA N 3 Purwokerto is the low skill of teachers in applying learning models that develop in this digital era. Knowledge about the various types of digital-based media that are developing is also still very lacking in teachers. For this reason, this activity aims to improve skills and knowledge in using learning models in the digital era through community service activities to improve skills in using learning models in the digital era. The methods of implementing this activity are seminar presentations, discussions, training, and mentoring. The result of this activity is that the skills of SMA N 3 Purwokerto teachers using learning models in the era are increasing, as well as knowledge about the types of learning models in the digital era is increasing.